Prototype Monitoring Dan Kontrol Kualitas Nilai Ph Air Pada Kapal : ( Teknologi Rekayasa Kelistrikan Kapal ) - Galuh Ayu Hapsari; Sri Mulyanto Herlambang; Arleiny Arleiny (Pusat Riset dan Inovasi Nasional, 2024)
Water is an important resource in daily life on board a ship. pH is a measure of the acidity or alkalinity of a solution, including water. The pH value ranges from 0 to 14, where a pH of 7 indicates a neutral solution, a pH value of less than 7 indicates an acidic solution, and a pH value of more than 7 indicates a basic solution. Therefore, it is important to have an effective monitoring and control system to ensure the pH value is safe and meets applicable standards. The method used in this research uses an experiment using an ESP32 microcontroller and the parameters used are a pH sensor to determine the pH value of the water on board the ship. The sensor provides data input to the ESP32. The data is processed and displayed on the LCD. In this system, if the pH of the water does not meet the standard, the ESP32 drives pump 1 or 2 to flow the acid or base solution. Testing on tools made to detect the pH value of water. The purpose of making this tool is to monitor and control water quality in order to avoid dangers that may arise due to exposure to water that is contaminated or with an inappropriate pH. This system can function well because there is an average error of 0.24% in testing between the pH sensor and the pH meter.